2021
DOI: 10.21037/atm-21-289
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses of PBRM1 in multiple cancer types and its association with clinical response to immunotherapy and immune infiltrates

Abstract: Background: The prognostic value of polybromo 1 (PBRM1) gene mutations in clear cell renal carcinoma (CCRCC) with anti-programmed death-ligand 1 (PD-L1) therapy remains controversial, and few studies have reported the impact of PBRM1 mutations in other cancer types. Methods:The patient information was obtained from cBioPortal and the Tumor Immune Estimation Resource (TIMER) databases. Mann-Whitney U test were used for correlation analysis. For survival analyses, Kaplan-Meier survival curves were used and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…However, mutations in PBRM1 have showed a negative impact on patient survival in ccRCC and BRCA (30)(31)(32).By comparing the effects of PBRM1 on OS and DFS in different tumors, we found that PBRM1 has significantly greater effects on ccRCC than in other tumors (Figure 3A). Some investigators have proposed PBRM1 as a target for therapy (33).…”
Section: Discussionmentioning
confidence: 93%
“…However, mutations in PBRM1 have showed a negative impact on patient survival in ccRCC and BRCA (30)(31)(32).By comparing the effects of PBRM1 on OS and DFS in different tumors, we found that PBRM1 has significantly greater effects on ccRCC than in other tumors (Figure 3A). Some investigators have proposed PBRM1 as a target for therapy (33).…”
Section: Discussionmentioning
confidence: 93%
“…PBRM1 (polybromo1) is a DNA binding protein that is required for cell cycle progression through mitosis. PBRM1 mutant patients have been reported to respond poorly to immunotherapy (Yang et al , 2021). Copy number analysis also revealed significant genomic heterogeneity, with Chr8 aneuploidy being the most common event (10 of 13 pairs; Fig 1D ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, mutations in PBRM1 associate with increased CTL infiltration and PD-L1 expression, as well as with decreased infiltration by regulatory T cells in clear cell renal cell carcinoma [84,85]. In addition, mutations in PBRM1 were also found predictive for worse clinical outcomes after PD-L1 blockade in various cancers, including clear cell renal cell carcinoma and lung adenocarcinoma, highlighting the ambiguous role of PBRM1 in immunity [86]. In chordomas, however, these findings suggest that alterations in the chromatin-remodeling complex, in part, could explain the extensive infiltration.…”
Section: The Tumor Microenvironment In Sarcomas With Complex Genomesmentioning
confidence: 99%